2016
DOI: 10.3945/an.116.012187
|View full text |Cite
|
Sign up to set email alerts
|

Omega-3 Polyunsaturated Fatty Acids and Oxylipins in Neuroinflammation and Management of Alzheimer Disease

Abstract: Alzheimer disease (AD) is becoming one of the most prevalent neurodegenerative conditions worldwide. Although the disease progression is becoming better understood, current medical interventions can only ameliorate some of the symptoms but cannot slow disease progression. Neuroinflammation plays an important role in the advancement of this disorder, and n-3 (ω-3) polyunsaturated fatty acids (PUFAs) are involved in both the reduction in and resolution of inflammation. These effects may be mediated by the anti-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
86
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(99 citation statements)
references
References 187 publications
(171 reference statements)
0
86
0
2
Order By: Relevance
“…The antioxidants in berries and the vitamin E in olive oil, green leafy vegetables and nuts could ease migraine by protecting the brain from oxidative stress [27]. Additionally, the omega-3 fatty acids found in sh may bene t migraine by lowering in ammation in the brain [28].…”
Section: Discussionmentioning
confidence: 99%
“…The antioxidants in berries and the vitamin E in olive oil, green leafy vegetables and nuts could ease migraine by protecting the brain from oxidative stress [27]. Additionally, the omega-3 fatty acids found in sh may bene t migraine by lowering in ammation in the brain [28].…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports demonstrates a significant association of ALA with dementia. Serum ALA level is inversely associated with risk of disabling dementia (Devassy, Leng, Gabbs, Monirujjaman, & Aukema, ; Yanai, ). AA is important in learning and memory and can increase neuronal firing in hippocampal neurons.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, studies on AD animal models have shown that dietary supplementation with PUFAs reduces Aβ deposition, improves cognition and reduces hippocampal neuronal loss or neurodegeneration. Studies have also been carried out on the active metabolites of EPA and DHA, such as the oxylipins, demonstrating their anti-inflammatory effects but above all their pro-resolving effects, i.e., their involvement in the resolution of the inflammatory process that does not seem to be regulated in AD [59,60]. Other studies have shown that mitochondrial dysfunction plays an important role in the pathogenesis of neurodegenerative diseases, in particular changes in the concentration and efficiency of the components of the respiratory complexes were reported.…”
Section: Polyunsaturated Fatty Acids (Pufa)mentioning
confidence: 99%